2002
DOI: 10.1007/s00449-001-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of exopolysaccharides in fouling phenomenon during ultrafiltration of microalgae ( Chlorella sp. and Porphyridium purpureum ): Advantage of a swirling decaying flow

Abstract: Ultrafiltration of two microalgae species, Chorellasp. and Porphyridium purpureum, has been performed in two filtration units of different configurations: a module generating a classical tangential-plane flow and another one inducing a swirling decaying flow. The swirling motion is generated by a unique tangential inlet at the bottom of an annulus. Permeation flux obtained in each ultrafiltration unit depends on the filtered species, and specific deposits are associated to each species and module. Enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It has been reported that many microalgae release large amount of RPS during growth [31], and most RPS can interfere with flocculation due to their complexation with multivalent metal ions [26,32]. However, some RPS are helpful to flocculation owing to the bridging mechanism [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that many microalgae release large amount of RPS during growth [31], and most RPS can interfere with flocculation due to their complexation with multivalent metal ions [26,32]. However, some RPS are helpful to flocculation owing to the bridging mechanism [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…9,11 In our study, the permeate flux decline could result in an increase in irreversible resistances that were generally related to the extracellular organic matters, including proteins, polysaccharides, and lipids released by microalgal cells during the crossflow filtration. 9,11,39 Table 3 shows EOM (protein + exopolysaccharides) content in the retentate, permeate, and rinse water sides after filtration processes. It can be observed that the amount of EOM in the retentate significantly increases with the increase in CFV.…”
Section: Effect Of Cfv On Microfiltration Permeate Flux and Membrane mentioning
confidence: 99%
“…As a result, higher amounts of cell debris and EOM released in the suspension caused severe membrane pore blockages. 12,39 The higher CFV of 6 m s −1 caused higher shear stress on microalgae cells during their passage through the valves, pumps, and the module, leading to higher EOM release. The EOM content in the rinse water at 6 m s −1 CFV is lower than that of 4 m s −1 , which suggests that a great part of the EOM released at 6 m s −1 CFV remains adhered on the membrane surface, leading to the higher irreversible resistances at 6 m s −1 .…”
Section: Effect Of Cfv On Microfiltration Permeate Flux and Membrane mentioning
confidence: 99%
“…It has been reported that algogenic organic matter (AOM) is involved in the reduction of flocculation efficiency in water treatment, and the inhibitory mechanism is that AOM can form complexes with cations in flocculant, which reduces the coagulation ability of the flocculant (Cheng and Chi 2003;Takaara et al 2007). Many microalgae release large amount of polysacchrides (RPSs) during growth (Morineau-Thomas et al 2002); however, no attention has yet been given to the influence of the RPS on the flocculation of microalgal cells with multivalent metal salts.…”
Section: Introductionmentioning
confidence: 99%